Hechtia rubicunda (Bromeliaceae; Hechtioideae), a new species from Oaxaca, México - López Ferrari, Ana Rosa; Espejo Serna, Adolfo (Instituto de Ecología, A.C., 2014)
Hechtia rubicunda, a new species from southeastern Oaxaca, Mexico is described and illustrated. The new taxon is compared with H. caudata L. B. Sm., H. fosteriana L. B. Sm., H. isthmusiana Burt Utley, and H. lanata L. B. Sm., species all described on the basis of material collected in this region.